Investigation of Structure-Property-Boiling Enhancement Mechanisms of Copper/Graphene Nanoplatelets Coatings - Rishi, Aniket M.; Rozati, Seyed Alireza; Trybus, Carole; Kandlikar, Satish G.; Gupta, Anju (Frontiers in Mechanical Engineering, 2021)
In this work, we present exceptionally high heat transfer coefficient and critical heat flux achieved by graphene nanoplatelets (GNP) and copper composite coatings with tunable surface properties. These coatings were created by a combination of powder metallurgy and manufacturing processes including ball milling, sintering, electrodeposition, and salt patterning. We demonstrated correlations between various coating processes, resultant surface morphologies and properties, improved boiling mechanism. Electrodeposition of GNP and copper particles led to formation of tall ridge like structures and valleys between to contain boiling fluid. Higher critical heat flux achieved on these coatings were attributed to the microlayer evaporation. It was observed that ball milling of GNP and copper particles prior to their sinter-coating enhanced their surface roughness that resulted in very high heat transfer coefficients nearly 5.4 times higher compared to plain copper surfaces. Additional salt-patterning along with sinter-coating yielded interconnected porous networks with high nucleating activity that led rendered record-breaking HTC of 1314 kW/m²-°C. Combination of these coating processes can be adopted to tailor the surfaces with e novel techniques developed in this work can be applied to a variety of thermal engineering applications.